Timing of Song Thrush Turdus philomelos on pre-nuptial migration in southern Italy - Scebba, Sergio; Castillo, Maria Oliveri Del (Ornis hungarica, 2017)
We studied the presence and movements of Song Thrush along the southern Tyrrhenian coast line in the region of Campania, from 2013 to 2016, in order to establish the timing of northward migration. We captured and ringed 150 birds with standardised mist-netting. There was little evidence of migration from the second 10-day period of January, when the trapping began, until the first 10-day period of February. There were no peaks due to the arrival of migrant birds though an increase in captures was recorded during the second 10-day period of February with a very considerable peak during the second 10-day period of March. The mean body mass showed significant increases from the third 10-day period of February, with the highest values recorded in March, also reflected in the accumulation of subcutaneous fat; 91% of subjects with fat scores 3 and 4 were concentrated between the third 10-day period of February and the third 10-day period of March, while the first birds with fat appeared only in the first 10-day period of February. Analysis of several recoveries of thrushes ringed in Campania, in other Italian regions and in other countries, confirms the presence of these birds in Campania in the period between the third 10-day period of January and the third 10-day period of March. The data gathered during the four years of this investigation provide a fairly clear, though not conclusive, picture of the temporal trend of pre-nuptial migration of Song Thrush, which never began before the second 10-day period of February, although it is possible that some birds on migration may be present in the previous 10-day period.